Influence of Intracellular Reactive Oxygen Species in Several Spermatozoa Activity in Indonesian Ongole Bull Cryopreserved Sperm - Prihantoko, Kurniawan Dwi (Science Publication, 2022)
Certain factors may affect sperm motility and integrity in a freezing process. Reactive Oxygen Species (ROS) is essential in damaging the sperm, as the previous study revealed that ROS is a major cause damaging the membrane of spermatozoa. This study aimed to understand ROS production and its interaction within the motility, mitochondrial activity and DNA damage to the cryopreservation process in Indonesian Ongole grade bull. A total of 40 ejaculated semen samples from four different bulls had taken. The ROS intracellularly detected by 2 -7 -Dichlorodihydrofluorescein Diacetate (DCFH-DA) and propodium iodide (PI). Mito Tracker Red kit was being used to discover the mitochondrial activity, while DNA sperms' integrity was detected by Terminal Deoxynucleotidyl Transferase dUTP Nick End Labeling (TUNEL). Examinations were done under a fluorescence microscope. Results of the study demonstrated a significant increase in ROS from fresh semen, diluted or equilibrated before being frozen (at 12°C and 4°C). ROS production showed no differences between frozen-thawed semen and thawed semen before the freezing process. A significant decrease in thawed semen had shown in membrane integrity and mitochondrial activity due to the equilibration process in which the temperature was significantly higher at 12°C and 4°C than the fresh semen temperatures, however, the diluting and freezing process had not given any significant causes to sperm DNA damage. This study concluded that ROS production with its effects might be the main factor that leads to the decreasing of sperm motility and integrity but no effect was discovered on DNA damage as the diluting and freezing process occurred. The results have proven the previous study which stated ROS has different mechanisms in affecting membrane integrity and DNA integrity. It also comes to the new theory that ROS might be affected by the chemical diluter despite the temperature of the freezing and thawing process.